THE SOCIAL STRUGGLE OF PRACTICES CONTEMPORARY RAJAH PANYENGKER IN BALI - Anadhi, I Made Gede; Suarka, I Nyoman; Sukiada, I Nyoman; Wijaya, I Nyoman (E-Journal of Cultural Studies; Volume 13, Number 1, February 2020DO - 10.24843/cs.2020.v13.i01.p04, 2020)
This study aims to analyze why there are practitioners today who still interpret Rajah Panyengker (mystical script) as a means of obtaining understanding, safety. Yet in reality they also practice Hindu religious rituals with the same purpose. The answers to these questions are sought in the arena of social struggle of practitioners Rajah Panyengker . In relation to their desire to emerge victorious in the arena of social and social struggle, they felt the need to convert capital so that they would not lose against their colleagues, fellow practitioners. The size of a practitioner's cultural capital is very dependent on his habitus. Therefore the answers to the research questions will be sought in the formation of the habitus of Rajah Panyengker practitioners. How the habitus forms the mystical cultural capital of practitioners regarding Rajah Panyengker , then places it in the arena of social struggle of the Balinese people today. Thus the focus of this study is directed at the meeting between the arenas of practitioners' internal social struggle with the users of Rajah Penyengker . Generative structural theory is used as a basis for thinking to understand and explain these problems. The conclusion of this study, that to emerge victorious in the arena of social struggle, practitioners fulfill the wishes of patients who want to get Rajah Penyengker . In the arena of social struggle like that, practitioners Rajah Panyengker do capital conversion. Thus this phenomenon illustrates the increasing arena of social struggle for practitioners of Rajah Penyenker today, not to search for positivistic origins or their backgrounds to interpret Rajah Penyengker .                                                       Keywords: Rajah Panyengker , social struggle, practitioners